THE COMMON USED OF FIGURATIVE LANGUAGES IN BEATLES’ MASTERPIECES - priyoto priyoto; panji armando (Journal of English Language and Literature (JELL), 2018)
This research is attempt to study about the common used of figurative languages in Beatles masterpieces. This research has three objectives: (1) to find out figurative languages in Beatles’ Masterpieces especially “A Day In The Life” and “A Hard Days Night” song, (2) to know what is the literal meaning in Beatles’ masterpieces especially “A Day In The Life” and “A Hard Days Night” song, (3) to know the moral values in Beatles’ masterpieces especially “A Day In The Life” and “A Hard Days Night” song . This research uses a descriptive qualitative method. The technique of data analysis is categorizing, sorting, coding, interpreting, drawing a conclusion, and representing the findings. The result of this research shows that The Beatles is common used hyperbole and pleonasm in both song lyrics. Based on the analysis, the writer hopes that this research can provide knowledge about figurative language that the readers can take positive things especially in works of art.